Mobile devices for content access in 2009: the Web, reading and libraries - Arroyo-Vázquez, Natalia (Anuario ThinkEPI, 2010)
The year we left behind was marked by a growing interest in mobile devices as a way to access content, from searching the internet to reading e-books. While we are in a time of incipient adoption of these devices, expectations placed on them include breaking the digital divide and becoming the main form of web access in the future. In the field of libraries, the initiatives in Spain are still timid and have set their sights mainly on the loan of e-book readers and content adaptation. A current outlook on mobile devices is sketched out, focusing on the Spanish area and the possibilities presented to its libraries.